PERAN STRATEGIS BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Irfansyah, Irfansyah (Ensiklopedia Sosial Review, 2021)
Consumer protection is any effort that ensures legal certainty to protect consumers. The legal basis that regulates consumer protection in Indonesia is Law Number 8 of 1999 concerning Consumer Protection. The method used in this research is normative legal research, using a statutory approach. According to Article 45 Paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection, it is emphasized that every consumer who is injured can sue business actors through an institution that is tasked with resolving disputes between consumers and business actors or through courts within the general court. In order to resolve consumer disputes outside the court, the government is mandated to establish a Consumer Dispute Resolution Agency. In handling and resolving consumer disputes, the Consumer Dispute Resolution Agency forms an assembly consisting of at least 3 (three) members representing elements of government, elements of consumers, and elements of business actors. According to Article 54 Paragraph (3) of Law Number 8 of 1999 concerning Consumer Protection, it is confirmed that the decision of the assembly formed by the Consumer Dispute Resolution Agency is final and binding. Settlement of disputes through the Consumer Dispute Resolution Agency doesn’t eliminate criminal responsibility so that the decision of the assembly formed by the Consumer Dispute Resolution Agency is sufficient initial evidence for investigators to carry out investigations.